2022
DOI: 10.1038/s41598-022-24820-3
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of hemodialysis related infections: a prospective multicenter study

Abstract: As in many countries, there is neither a surveillance system nor a study to reveal the hemodialysis (HD) related infection rates in Turkey. We aimed to investigate the infection rate among HD outpatients and implement CDC’s surveillance system. A multicenter prospective surveillance study is performed to investigate the infection rate among HD patients. CDC National Healthcare Safety Network (NHSN) dialysis event (DE) protocol is adopted for definitions and reporting. During April 2016–April 2018, 9 centers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
3
2
0
Order By: Relevance
“…Moreover, it was found that S. aureus was the most common pathogen for CVC infection. This finding is consistent with many other studies 5,14,15 , however S. aureus in this study was non-resistant to methicillin.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, it was found that S. aureus was the most common pathogen for CVC infection. This finding is consistent with many other studies 5,14,15 , however S. aureus in this study was non-resistant to methicillin.…”
Section: Discussionsupporting
confidence: 94%
“…This contrasted with CVC, which had the lowest prevalence but the highest incidence of all events. This was comparable to other studies [13][14][15] and the NHSN 5 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among these cases, 46 (62.2%) were de nitive/probable CRBSIs and 28 (37.8%) were culture negative possible CRBSIs(7). WhileBhojaraja et al, (2022), in a study conducted on 882 Patients aged ≥ 18 with 921 catheters either on maintenance HD or with acute kidney injury, reported 212 (23%) had Our results regarding the higher rate of infections in NTVCs and in TVCs, compared to AVFs, though insigni cant in TVCs are comparable with the results ofHasanoglu et al, (2022), a multicenter prospective surveillance study in Turkey. They reported that the risk of bacteremia was 17.6 times higher in patients of different ages receiving HD via CVC, than the patients with AVF (9) Mohamed et al, (2019).…”
supporting
confidence: 71%
“…* days from the start of the study for old vascular access inserted before the study or days from insertion for new vascular access inserted during the study till non-functioning or the end of the study Table (6): Incidence of infection per 1000 vascular access days in the 2nd year * days from the start of the study for old vascular access inserted before the study or days from insertion for new vascular access inserted during the study till non-functioning or the end of the study Incidence of different types of infection in 1000 catheter days as well as a comparison between rst and second years of the study regarding vascular access status are shown in tables (7), (8) and(9). Table(7): Incidence of different types of catheter related infections per 1000 catheter days in the rst year P1: Comparison between CRBSI vs. Exit site infections P2: Comparison between CRBSI vs.…”
mentioning
confidence: 99%